Stability Analysis and Reasonable Layout of Floor Drainage Roadway above Confined Water and under Mining Influence. (12th March 2021) - Guo, Xiaofei; Li, Yongen; Zhou, Guangdong; He, Zengji; Yu, Haoran; Xu, Yichang
Abstract : The surrounding rock failure range of floor drainage roadway under the mining influence and its effect on the aquiclude are the key to determine the aquiclude thickness of the floor. This paper studied the distribution characteristics of the surrounding rock plastic zone by the numerical simulation when the floor drainage roadway was located at different positions under the working face and determined the rational position. Results show that (1) when the floor drainage roadway is staggered inward, the floor surrounding rock is prone to appear the butterfly plastic zone under single work face mining. And the butterfly plastic zone increases sharply after being affected by secondary mining of adjacent working face. (2) When the floor drainage roadway is staggered outward, the floor surrounding rock plastic zone extends gently affected by a single working face. And the depth of the plastic zone has no obvious change after being affected by secondary mining of adjacent working face. (3) According to the risk of water inrush, the three layout schemes can be ranked as follows: stagger   inward   25   m > stagger   inward   80   m > stagger   outward   15   m . (4) Considering the floor stress environment, gas extraction efficiency, and water prevention and control, the reasonable location of floor drainage roadway below the No. 11060 working face of Zhaogu No. 2 Coal Mine was finally determined. It was arranged in the sandy mudstone layer on the upper part of L9 limestone under the middle part of coal pillar and was drived along the seam floor.